2014
DOI: 10.1089/ten.tea.2013.0249
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of Matrix Stiffness and Vascular Endothelial Growth Factor on Mesenchymal Stem Cells for Vascular Endothelial Regeneration

Abstract: Mesenchymal stem cells (MSCs) hold tremendous potential for vascular tissue regeneration. Research has demonstrated that individual factors in the cell microenvironment such as matrix elasticity and growth factors regulate MSC differentiation to vascular lineage. However, it is not well understood how matrix elasticity and growth factors combine to direct the MSC fate. This study examines the combined effects of matrix elasticity and vascular endothelial growth factor (VEGF) on both MSC differentiation into en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…For this work, we chose a soft, fibrous hydrogel platform prepared from an electrospinning method as previously described [8, 15]. Recent studies have highlighted the importance of 3-dimensional, fibrous matrices to optimize stem cell niche environments [24, 25], as well as their candidacy as platforms for MSC differentiation into vascular lineages [8, 15]. We find electrospinning, followed by UV polymerization to represent a highly versatile technique whereby stiffness and microstructure can be reproduced with high fidelity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this work, we chose a soft, fibrous hydrogel platform prepared from an electrospinning method as previously described [8, 15]. Recent studies have highlighted the importance of 3-dimensional, fibrous matrices to optimize stem cell niche environments [24, 25], as well as their candidacy as platforms for MSC differentiation into vascular lineages [8, 15]. We find electrospinning, followed by UV polymerization to represent a highly versatile technique whereby stiffness and microstructure can be reproduced with high fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have observed the differentiation of MSCs into vascular lineages in vitro [36, 37]. The majority of literature regarding stem cell differentiation into vascular lineages involves precise soluble factor regiment [36,], application of shear [38], matrix rigidity [8, 15], composition of the ECM [3941], or multiple factors [15, 42]. For example, it has been shown that the administration of vascular endothelial growth factor (VEGF) [36] or combination with shear stress [43] or matrix elasticity [15] instructs MSC differentiation into vascular lineages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major next step will be to understand how these two classes of inputs are integrated to direct NSC behavior under physiological conditions, as well as how they can go awry in disease or injury. Encouragingly, there have already been studies that have reported the synergistic effect of tuned matrix stiffness and biochemical stimulation in MSCs [76, 77]. However, current culture platforms preclude high-throughput study of the additional parameter space.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…One study implicated the potential role of low stiffness (2 kPa) in directing MSC toward an EC versus an SMC fate, although it is unclear whether it is the nanofibrous architecture compared with polystyrene culture dishes or the signaling from lower stiffness of the nanofibers that might be directing EC fate [187]. Although there is little direct evidence to date that stiffness guides mural fate, it is well known that stiffness can modulate a progenitor's shape, cytoskeletal organization, and consequently its differentiation (reviewed in depth by Reilly et al [188]).…”
Section: Mechanical Signaling and The Ecmmentioning
confidence: 99%